Recommendations for nasotracheal tube insertion depths in neonates - Ebenebe, Chinedu Ulrich; Schriever, Kristina; Wolf, Monika; Herrmann, Jochen; Singer, Dominique; Deindl, Philipp (Frontiers in Pediatrics, 2022)
Background Endotracheal tube (ETT) malposition is common in neonatal intubation. Recommendations for ETT insertion depths predominantly address orotracheal intubation. The aim of this study was to develop gestational age-, weight-, and length-based curve charts and tables for nasotracheal ETT insertion depth recommendations in neonates. Method In this retrospective single-center study, the individual optimal ETT insertion depths in neonates were determined by evaluating postintubation radiographic images. Gestational age-, weight-, and length-based best-fit curves and tables were generated using regression analysis to calculate related ETT insertion depths. The insertion depths predicted by the models were compared with previously published recommendations. Results We analysed intubations of 178 neonates (gestational age range at intubation: 23.7–43.0 weeks). Applying sigmoidal logistic regression models, curves and tables revealed R squared values between 0.766 and 0.837. The insertion depths predicted by the models revealed certain deviations when compared with three previously published recommendations for nasotracheal ETT depth estimation in neonates. Conclusions The charts and tables developed in this study enable a fast and accurate determination of recommended nasotracheal ETT insertion depths in neonates.